2011
DOI: 10.1212/wnl.0b013e318233b36a
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic detection of fasciculations markedly increases diagnostic sensitivity of ALS

Abstract: Objectives:To study the utility of muscle ultrasound (US) for detection of fasciculations and its contribution to diagnosis in amyotrophic lateral sclerosis (ALS). Fasciculations are characteristic features of ALS, and US can detect them easily and reliably. New diagnostic criteria for ALS, the Awaji algorithm, reintroduced fasciculations as evidence of acute denervation equivalent to that of fibrillations and positive sharp waves. Methods:In 81 consecutive patients with sporadic ALS, we prospectively performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
111
1
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(135 citation statements)
references
References 34 publications
(11 reference statements)
5
111
1
8
Order By: Relevance
“…The patient was observed for two minutes without moving the probe to detect fasciculations of the tongue muscle. While the patients were relaxed, we diagnosed any involuntary twitching of small parts of the tongue muscle as fasciculation and confirmed that the muscle fired irregularly, as reported previously (Misawa et al, 2011). The total tongue sonography examination took at most five minutes.…”
Section: Tongue Sonographysupporting
confidence: 86%
See 1 more Smart Citation
“…The patient was observed for two minutes without moving the probe to detect fasciculations of the tongue muscle. While the patients were relaxed, we diagnosed any involuntary twitching of small parts of the tongue muscle as fasciculation and confirmed that the muscle fired irregularly, as reported previously (Misawa et al, 2011). The total tongue sonography examination took at most five minutes.…”
Section: Tongue Sonographysupporting
confidence: 86%
“…In the diagnosis of early stage ALS, fasciculations are important indicators of acute denervation according to the Awaji criteria (de Carvalho et al, 2008). Misawa et al reported substantially more frequent detection of fasciculations in the tongue, biceps brachii and tibialis anterior muscles using ultrasonography compared with electromyography and found that the rate of accurate ALS diagnosis increased using ultrasonography with the Awaji criteria (Misawa et al, 2011). In this study, we also recognized ultrasonography as superior for diagnosing fasciculations in ALS patients.…”
Section: Discussionsupporting
confidence: 61%
“…Detection of axonal degeneration by needle electromyography could be much greater than sonographic evaluation of axonal thinning. A note should be made, however, on muscle sonography because sonography would have greater sensitivity for detection of fasciculations than needle electromyography (14). Second, on the other hand, our data also suggest potential utility of sonography to detect subtle axon loss in clinically relatively preserved regions, because of similar axon sizes between the arm-onset and the leg-onset groups.…”
Section: Clinical Significancementioning
confidence: 72%
“…The diagnostic importance of spontaneous EMG activity is especially true for fasciculation potentials, which can be profuse very early in the disease, revealing an increased instability of motor unit excitability anticipating the denervation-reinnervation process [20,23,27]. It has even been proposed to use muscle ultrasonography techniques to increase the sensitivity of fasciculation detection in patients with ALS [4,47,68]. In addition, an abundant literature has emphasized the differential characteristics of fasciculation potentials in ALS compared to other clinical conditions.…”
Section: The Value Of Spontaneous Emg Activitymentioning
confidence: 99%